2010
DOI: 10.1051/forest/2010039
|View full text |Cite
|
Sign up to set email alerts
|

Plantation forestry diseases in Zambia: Contributing factors and management options

Abstract: Abstract• Plantation forestry in Zambia is based mainly on non-native Eucalyptus and Pinus species and constitutes an important component of the country's economy. The productivity of these plantations is, however, threatened by several factors, including fungal pathogens that reduce timber quality and cause tree mortality.• In this paper we present a review of diseases affecting plantation forestry and highlight factors that may favour their development and severity in the country.• Plantation health manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
1
7
0
1
Order By: Relevance
“…; Chungu et al. ) while T. gauchensis was known to cause the same disease in Uganda and Ethiopia in East Africa (Gezahgne et al. ; Roux et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chungu et al. ) while T. gauchensis was known to cause the same disease in Uganda and Ethiopia in East Africa (Gezahgne et al. ; Roux et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Chungu et al. ). Teratosphaeria gauchensis is known from Africa, North and South America (Gezahgne et al.…”
Section: Introductionmentioning
confidence: 97%
“…ex Munk (anamorph: Dothistroma septosporum (Dorog.) M. Morelet) на плантаціях сосни променистої (P. radiata D. Don) (Chungu, Muimba-Kankolongo, Wingfi eld, & Roux, 2010);…”
Section: повернення назад (Spill-back)unclassified
“…All DNA sequences used in this study were used in previous phylogenetic analyses (Chungu et al 2010;Crous et al 2004;Gezahgne et al 2006;Hunter et al 2009;Pérez et al 2009aPérez et al , b, 2010Pérez et al , 2012 and were downloaded from GenBank (http://www. ncbi.nlm.nih.gov; Table 1).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…For phylogenetic analyses, 21 isolates were selected to represent the global intraspecific diversity previously described for T. nubilosa (Chungu et al 2010;Crous et al 2004;Gezahgne et al 2006;Hunter et al 2009) and the three native population groups identified based on microsatellite marker analyses (Pérez et al 2012). Phylogenetic analyses included the exepitype specimen of T. nubilosa, isolate CMW 3282 (= CPC 937, = CBS 116005) from Victoria, Australia, designated by Crous et al (2004).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%